The Trend to Close a Sexual Trade Localization: The Shifted Model of Religiosity in Dolly, Surabaya - Taufiqurrohim Taufiqurrohim (IJoIS: Indonesian Journal of Islamic Studies, 2025)
Before June 2014, Dolly is well known as the biggest prostitute location in East Java and even in Southeast Asia. But now, Dolly is exchanged to the religious zone and economic center both by the government and such social organizations. So, this paper tries to explain how shifting models of religiosity in sexual prostitute localization, specifically in ‘Dolly’ Surabaya. The researcher uses an ethnographical methodology of the research by configuring observational data combined with deep interview of the object containing the government, religious elite, local people and sexual prostitute actors. So, this paper firstly contains with the former dolly description as the locus of sex trade before it closed officially by government. Then it continues to re-question about how religion comes as a strategy to change prostitute location. And at the last, the writing discusses about process of negotiation of faith and the current religious life of the former sex trade location. The research finds that (1) there is a specific model of religiosity negotiated in localization to change the sexual prostitute to be more religious place. (2) The religionization of ‘dolly’ through how local inhabitants and organizations implementing faith negotiation. (3) The government with locals gives an awareness to ‘rethinking’ about sexual prostitution as the way of life through promoting Mbah Kapiluddin pilgrims. By this case, the writer argues that the sex trade has a contrasting idea with the religious life so the more strengthens religious promotion, the more prostitute decreases with the process of tackled negotiation.